2018
DOI: 10.1038/gim.2017.173
|View full text |Cite
|
Sign up to set email alerts
|

Genomic study of severe fetal anomalies and discovery of GREB1L mutations in renal agenesis

Abstract: Our study opens a window on the distinctive genetic landscape associated with fetal anomalies and highlights the power-but also the challenges-of WES in prenatal diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
73
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 42 publications
(44 reference statements)
4
73
1
1
Order By: Relevance
“…To date, the highest diagnostic yield for prenatal WES has been in fetuses with multiple anomalies or specific types of anomalies, such as structural brain malformations, 7,8 with diagnostic rates that are similar to those reported in the study by Boissel et al 5 Furthermore, trio testing has a slightly higher diagnostic yield compared with proband-only testing, particularly for sporadic fetal findings in the absence of parental consanguinity or a family history of similar findings. Such cases are highly selected with a greater a priori risk that the fetus has a single-gene condition.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…To date, the highest diagnostic yield for prenatal WES has been in fetuses with multiple anomalies or specific types of anomalies, such as structural brain malformations, 7,8 with diagnostic rates that are similar to those reported in the study by Boissel et al 5 Furthermore, trio testing has a slightly higher diagnostic yield compared with proband-only testing, particularly for sporadic fetal findings in the absence of parental consanguinity or a family history of similar findings. Such cases are highly selected with a greater a priori risk that the fetus has a single-gene condition.…”
supporting
confidence: 71%
“…Unlike the initial implementation of targeted chromosomal microarray into prenatal testing, it may be more difficult to target genomic testing to solely known pathogenic variants in known disease-causing genes. This will certainly decrease diagnostic yield, particularly for those conditions caused by pathogenic missense variants that have not been reported previously or pathogenic variants in novel disease genes, such as Boissel et al 5 found with GREB1L.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…FKPB8 was proposed as a candidate gene based on the reported phenotype of FKBP8 −/− mice which includes VD and scoliosis (Shirane, Ogawa, Motoyama, & Nakayama, ). Two fetuses whose VD had been identified on postmortem skeletal survey were diagnosed with the following syndromes: Raine syndrome (a lethal hyperostosis syndrome) and Currarino syndrome (which associates partial sacral agenesis, a presacral mass, and anorectal malformation; Boissel et al, ). Medical genetics referral is therefore indicated to look for non‐chromosomal causes, especially for non‐isolated cases.…”
Section: Discussionmentioning
confidence: 99%